Medusas, Bestiaries and Theatralities in the Contemporary World - Castillejo Cuellar, Alejandro; Profesor Asociado. Investigador Asociado, Centro para la Paz y la Memoria. (Editorial Pontificia Universidad Javeriana, 2007)
A different lecture in regards to conceptions about man is the one we will call “pendular”: the concept of “man” raises a polarity about the way we apprehend it, especially in a culture that has given origin to science as the primordial method to approach the universe. Is totality, as Euclidian axioms prescribe, the sum of the parts? Could our “habits of thought” permit a universe in which the fragments of totality “add to more” than that same totality? What is the relationship, in summary, between the totality and its constituting fragments? In this text, we will explore the idea of the world as an appearance of alterities. We will meditate about a way in which this process could have an effect on how the human being inhabits space.